DEATH ACCEPTANCE AND RELIGIOUS BELIEF PROMOTE DEATH PREPARATION IN OLD AGE ONLY IN GERMAN AND U.S., BUT NOT IN HONG KONG. (11th November 2018) - Fung, H H; Lu, M; Tse, D C K
Abstract: Global aging poses increasing demand on the practice of death preparation. This study investigates cultural differences in death preparation. 240 participants from Hong Kong (aged 36–86), 159 from Germany (aged 19–83), and 97 from the United States (aged 26–84) completed two longitudinal surveys on death preparation, death acceptance, and religious belief. For participants in the Western countries (Germany and the United States), age was positively associated with death preparation two years later (b = .55, p < .01). This relationship, however, was not observed among East Asian (Hong Kong) participants (p > .25). Further analyses revealed that stronger religious belief and higher death acceptance mediated the relationship between age and death preparation among Westerners only. These findings indicate that the age-related increase in religiosity and death acceptance may promote death preparation in Western cultures but not in East Asian cultures.